Shear stress and plaque microenvironment induce heterogeneity: A multiscale microenvironment evolution model. (June 2023) - Pan, Jichao; Cai, Yan; Wu, Jie; Lu, Yunhao; Li, Zhiyong
Highlights: A multiscale model involving CFD, microenvironment evolution and cellular activities is built. The multiscale microenvironment model reveals the role of wall shear stress and microenvironment in plaque evolution, and how they together influence plaque heterogeneity. Plaque heterogeneity can be reduced by decreasing low WSS area at downstream, as well as by altering the phagocytic abilities of macrophage on lipoproteins. Abstract: Background: Both clinical images and in vivo observations have demonstrated the heterogeneity in atherosclerotic plaque composition. However, the quantitative mechanisms that contribute to the heterogeneity, such as the wall shear stress (WSS) and the interplays among microenvironmental factors are still unclear. Methods: We develop a multiscale model coupling computational fluid dynamics, interactions of microenvironmental factors and evolutions of cellular behaviors to investigate the formation of plaque heterogeneity in a three-dimensional vessel segment. The model involves WSS, lipid deposition and inflammatory response to reveal the dynamic balance existed between the lipid metabolism and the phagocytosis of macrophages. Results: The dynamic balance in microenvironment is influenced by both the WSS and the interactions with microenvironmental factors, and consequently results in the longitudinal heterogeneity observed in plaque pathology. In addition, plaque heterogeneity can be reduced by decreasing low WSS area at downstream, as well as by altering the phagocytic abilities of macrophage on lipoproteins, which may be used to develop future plaque regression strategies. Conclusions: This multiscale modeling provides a framework to understand the mechanisms in dynamics of plaque composition and also provides quantitative information to better risk stratification of plaque vulnerability in future clinical practice.